Generalization Contractive Mappings on Rectangular b-Metric Space - Jayshree Patil; Basel Hardan; Ahmed A. Hamoud; Amol Bachhav; Homan Emadifar; Hatira Günerhan (Advances in Mathematical Physics)
In this paper, we introduce new coincidence fixed point theorems for generalized ϕ,ψ-contractive mappings fulfilling kind of an admissibility provision in a Hausdorff b-rectangular metric space with the support of C-functions. We applied our results to establish the existence of a solution for some integralitions. Finally, an example is presented to clarify our theorem.